Neuropsychological Evaluation of Children and Adolescents With Acute Carbon Monoxide Poisoning. Issue 5 (May 2016) - Karaman, Dursun; Metin, Suleyman; Kara, Koray; Ozdemir, Adem; Yildiz, Senol; Durukan, Ibrahim; Almbaidheen, Mahmoud; Uzun, Gunalp; Turkbay, Tumer
Abstract : Objectives: Carbon monoxide (CO) poisoning is a worldwide health problem. We have limited information regarding psychological adversities of CO poisoning in children and adolescents. The aim of this study was (1) to investigate the effects of severe CO poisoning on cognitive functions, mood, and behaviors in children and adolescents and (2) to identify factors related to occurrence of neuropsychological symptoms. Methods: This study included pediatric patients, who were evaluated after CO poisoning at the Department of Child and Adolescent Psychiatry between January 2012 and April 2013. The patients were evaluated at 2 time points. The first evaluation was done when they were discharged from emergency department, and the second evaluation was done 1 month after CO poisoning. Turkish versions of internationally recognized tests were used to evaluate anxiety, depressive symptoms, attention, visual-spatial skills, memory, and behaviors of patients. Results: Twenty-seven patients were analyzed. The mean age of the patients was 11.8 ± 2.7 years (range, 6–18 years). The mean carboxyhemoglobin level was 31.5% ± 7.8% (range, 19%–51%) dir. Delayed neurological sequel was observed in only 1 patient, who had headache and tinnitus. We found that carboxyhemoglobin level was not correlated with later neuropsychiatric test scores. However, we found a correlation between history of loss of consciousness and anxiety symptom level, hyperbaric oxygen (HBO) therapy session and behavioral problems, and time to HBO therapy and attention problems. Conclusions: We suggest that CO exposure duration, history of loss of consciousness, time to HBO therapy, and the number of HBO therapy session affect neuropsychological symptom levels and occurrence of attention and behavioral problems.